Erecting the Staggered-truss System: A View from the Field - Hassler, Arthur E. (Engineering Journal, 1986)
The staggered-steel truss system has been used as the major supporting element for many years. Projects using this truss system are economical, easy to fabricate and erect. and as a result beat out all other framing systems. This paper deals with a building recently completed which used the staggered steel truss system. The project is the Resorts International Hotel in Atlantic City, N.J.